Integrating perspectives: contributions of Gestalt Theory to the understanding of Social Psychology - Gamboa, Alfredo Javier Pérez; Egües, Miguel Alejandro Pérez (AWARI, 2023)
This article provides a comprehensive review of the significant contributions of Gestalt Theory to Social Psychology. It highlights how this perspective enriches the understanding of perception, cognition and social interaction. Originating in the field of perceptual psychology, Gestalt Theory postulates that individuals perceive visual and social elements as integrated parts of a whole, rather than sums of isolated components. This holistic principle is explored through its application in Social Psychology. How it influences impression formation, problem solving, decision making and group dynamics is examined. Key concepts such as insight thinking, figure background in social perception, and the importance of patterns and structures in interpreting social contexts are discussed. In addition, the impact of Gestalt Theory on research methods and social therapies is evaluated from a unique perspective on human interaction and group behavior. Finally, future research areas are suggested that could benefit from a deeper integration of Gestalt principles into Social Psychology, promoting a more holistic and dynamic approach to understanding the mind and social behavior.